P. 1

# High School Mathematics Grade 10-12

4.77

|Views: 35,091|Likes:
The Free High School Science Texts: Textbooks for High School Students Studying the Sciences Physics Grade 12 Copyright c 2007 “Free High School Science Texts” Permission is granted to copy, distribute and/or modify this document under the terms of the GNU Free Documentation License, Version 1.2 or any later version published by the Free Software Foundation; with no Invariant Sections, no Front- Cover Texts, and no Back-Cover Texts. A copy of the license is included in the section entitled “GNU Free Documentation License” Webpage: http://www.fhsst.org/
The Free High School Science Texts: Textbooks for High School Students Studying the Sciences Physics Grade 12 Copyright c 2007 “Free High School Science Texts” Permission is granted to copy, distribute and/or modify this document under the terms of the GNU Free Documentation License, Version 1.2 or any later version published by the Free Software Foundation; with no Invariant Sections, no Front- Cover Texts, and no Back-Cover Texts. A copy of the license is included in the section entitled “GNU Free Documentation License” Webpage: http://www.fhsst.org/

### Availability:

See more
See less

10/14/2014

pdf

text

original

A quadratic sequence is a sequence of numbers in which the second diﬀerences between
each consecutive term diﬀer by the same amount, called a common second diﬀerence.

For example,

1; 2; 4; 7; 11; ...

(20.1)

is a quadratic sequence. Let us see why ...

If we take the diﬀerence between consecutive terms, then:

a2−a1 = 2−1 = 1

a3−a2 = 4−2 = 2

a4−a3 = 7−4 = 3

a5−a4 = 11−7 = 4

We then work out the second diﬀerences, which is simply obtained by taking the diﬀerence

between the consecutive diﬀerences {1; 2; 3; 4; ...} obtained above:

2−1 = 1

3−2 = 1

4−3 = 1

...

We then see that the second diﬀerences are equal to 1. Thus, (20.1) is a quadratic sequence.

Note that the diﬀerences between consecutive terms (that is, the ﬁrst diﬀerences) of a quadratic
sequence form a sequence where there is a constant diﬀerence between consecutive terms. In

the above example, the sequence of {1; 2; 3; 4; ...}, which is formed by taking the diﬀerences

between consecutive terms of (20.1), has a linear formula of the kind ax+b.

265

20.2

The following are also examples of quadratic sequences:

3; 6; 10; 15; 21; ...

4; 9; 16; 25; 36; ...

7; 17; 31; 49; 71; ...

2; 10; 26; 50; 82; ...

31; 30; 27; 22; 15; ...

Can you calculate the common second diﬀerence for each of the above examples?

Question: Write down the next two terms and ﬁnd a formula for the nth

term of

the sequence 5,12,23,38,...,...,

Step 1 : Find the ﬁrst diﬀerences between the terms.

i.e. 7,11,15

Step 2 : Find the 2nd diﬀerences between the terms.

the second diﬀerence is 4.

So continuing the sequence, the diﬀerences between each term will be:

15 + 4 = 19

19 + 4 = 23

Step 3 : Finding the next two terms.

So the next two terms in the sequence willl be:

38 + 19 = 57

57 + 23 = 80

So the sequence will be: 5,12,23,38,57,80

Step 4 : We now need to ﬁnd the formula for this sequence.

We know that the ﬁrst diﬀerence is 4. The start of the formula will therefore be

2n2

.

Step 5 : We now need to work out the next part of the sequence.

If n = 1, you have to get the value of term 1, which is 5 in this particular sequence.

The diﬀerence between 2n2

= 2 and original number (5) is 3, which leads to n+ 2.

Check is it works for the second term, i.e. when n = 2.
Then 2n2

= 8. The diﬀerence between term 2( 12) and 8 is 4, which is can be

written as n+ 2.
So for the sequence 5,12,23,38,... the formula for the nt

h term is 2n2

+n+ 2.

General Case

If the sequence is quadratic, the nt

h term should be Tn = an2

+bn+c

TERMS a +b+c

4a+ 2b+c

9a+ 3b+c

1st

diﬀerence

3a+b

5a+b

7a+b

2nd

diﬀerence

2a

2a

In each case, the 2nd diﬀerence is 2a. This fact can be used to ﬁnd a, then b then c.

266

20.2

Question: The following sequence is quadratic: 8,22,42,68,... Find the rule.

Step 1 : Assume that the rule is
an2

+bn+c

TERMS 8

22

42

68

1st

diﬀerence 14

20

26

2nd

diﬀerence

6

6

6

Step 2 : Determine values for a,b and c

Then 2a = 6 which gives a = 3

And 3a+b = 14→9 +b = 14→b = 5

And a+b+c = 8→3 + 5 +c = 8→c = 0

Step 3 : Find the rule

The rule is therefore: nt

h term = 3n2

+ 5n

For

n = 1,1st term = 3(1)2

+ 5(1) = 8

n = 2,2nd term = 3(2)2

+ 5(2) = 22

n = 3,3rd term = 3(3)2

+ 5(3) = 42

Extension: Derivation of the nth

Let the nth

-term for a quadratic sequence be given by

an = A·n2

+B·n+C

(20.2)

where A, B and C are some constants to be determined.

an = A·n2

+B·n+C

(20.3)

a1 = A(1)2

+B(1) +C = A+B +C

(20.4)

a2 = A(2)2

+B(2) +C = 4A+ 2B +C

(20.5)

a3 = A(3)2

+B(3) +C = 9A+ 3B +C

(20.6)

Let d ≡ a2−a1

∴d = 3A+B

⇒B = d−3A

(20.7)

The common second diﬀerence is obtained from

D = (a3−a2)−(a2−a1)

= (5A+B)−(3A+B)

= 2A

⇒A = D
2

(20.8)

Therefore, from (20.7),

B = d− 3

2 ·D

(20.9)

267

20.2

From (20.4),

C = a1−(A+B) = a1− D

2 −d+ 3

2 ·D

∴C = a1 +D−d

(20.10)

Finally, the general equation for the nth

-term of a quadratic sequence is given by

an = D

2 ·n2

+ (d− 3

2 D)·n+ (a1−d+D)

(20.11)

Worked Example 95: Using a set of equations

Question: Study the following pattern: 1; 7; 19; 37; 61; ...

1. What is the next number in the sequence ?

2. Use variables to write an algebraic statement to generalise the pattern.

3. What will the 100th term of the sequence be ?

Step 1 : The next number in the sequence

The numbers go up in multiples of 6

1 + 6 = 7, then 7 + 12 = 19

Therefore 61 + 6×6 = 97
The next number in the sequence is 97.

Step 2 : Generalising the pattern

TERMS 1 7

19

37

61

1st

diﬀerence 6 12

18

24

2nd

diﬀerence

6

6

6

6

The pattern will yield a quadratic equation since second diﬀerence is constant

Therefore an2

+bn+c = y
For the ﬁrst term: n = 1, then y = 1

For the second term: n = 2, then y = 7

For the third term: n = 3, then y = 19
etc....

Step 3 : Setting up sets of equations

a+b+c = 1

(20.12)

4a+ 2b+c = 7

(20.13)

9a+ 3b+c = 19

(20.14)

Step 4 : Solve the sets of equations

eqn(2)−eqn(1) : 3a+b = 6

(20.15)

eqn(3)−eqn(2) : 5a+b = 12

(20.16)

eqn(5)−eqn(4) : 2a = 6

(20.17)

Therefore a = 3,b =−3 and c = 1

(20.18)

The general formula for the pattern is 3n2

−3n+ 1

Step 6 : Term 100

Substitude n with 100:

3(100)2

−3(100)+ 1 = 29 701

The value for term 100 is 29 701.

268

20.3

Extension: Plotting a graph of terms of a quadratic sequence

Plotting an vs. n for a quadratic sequence yields a parabolic graph.

3; 6; 10; 15; 21; ...

If we plot each of the terms vs. the corresponding index, we obtain a graph of a

parabola.

Term

,an

y-intercept, a1

1 2 3 4 5 6 7 8 9 10

Index, n

a1

a2

a3

a4

a5

a6

a7

a8

a9

a10

scribd
/*********** DO NOT ALTER ANYTHING BELOW THIS LINE ! ************/ var s_code=s.t();if(s_code)document.write(s_code)//-->